Two new species of the genus Maaserphus Lin, 1988 (Hymenoptera: Proctotrupidae) from Japan and Taiwan - Abe, Junta (Zootaxa, 2024)
Maaserphus bunun Abe, sp. nov. and M. yamagishii Abe, sp. nov. are described from Japan and Taiwan. Two known species of this genus, M. flavitarsis He & Xu, 2015 and M. striatus Lin, 1988, are newly recorded from Japan.